On Regularity Criteria for the Two-Dimensional Generalized Liquid Crystal Model - Yanan Wang; Zaihong Jiang (Abstract and Applied Analysis)
We establish the regularity criteria for the two-dimensional generalized liquid crystal model. It turns out that the global existence results satisfy our regularity criteria naturally.